“A satire is when it’s the same as here but there’s animals in it”: Review of Robert McKay and Susan McHugh, eds., Animal Satire - Quinn, Emelia (Humanimalia, 2024)
Review of:Robert McKay and Susan McHugh, eds., Animal Satire. Palgrave Studies in Animals and Literature. Cham: Palgrave Macmillan, 2023. xii + 431 pp. 14 illus. $159.99 (hb).